Entrepreneurial Intention of Sari Mutiara Indonesia University Student In Medan - Rosanna Purba (Journal of Accounting Auditing and Business, 2019)
This study examined factors that influence entrepreneurial intention of college students by using the analysis model that consists of three factors namely personality factors, contextual factors, and demography factors in Sari Mutiara Indonesia University.  Research using survey questionnaires data collection by using an accidental sampling technique with the samples of this research are all the students as much 360 students from 20 different majors. Results of this study showed that : (1) There is a significant effect between the personality factors, such as locus of control and need for achievement with entrepreneurial intention of college students; (2) There is a significant effect between the contextual factors, such as subjective norms and instrumental readiness with entrepreneurial intention of college students; and otherwise (3) There is no effect of demographic factors on the entrepreneurial intention of college students.